Wind Turbine for Power Generation and Storage by Vehicular Movement on Highways with IoT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The demand for energy is increasing tremendously with each passing day. The depletion of the energy resources has necessitated the usage of renewable sources to meet the energy crisis the entire world is facing. The most important of all the renewable sources is wind which can be used as an efficient means for generating electricity by using wind turbines. These turbines are employed for the transformation of mechanical energy to electrical energy, thus making the use of a renewable source rather than relying on conventional sources of energy. The current work discusses the fabrication, erection and installation of a wind turbine on a highway which generates power using the vehicular movement. In this study, traffic survey was conducted at different locations to select the best location to set up the turbine giving due consideration to wind speed, vehicular movement and traffic volume. The fabricated wind turbine was installed at the site chosen based on the traffic studies carried out. The power generated was calculated by noting the current and voltage. The power generated was stored in a 12V, 1.3AH battery. The IoT system was installed with the turbine and sensors to record the voltage, current and any faults in the turbine. A boost converter was used which proved to be an asset in amplifying the voltage.